FITOPLANKTON DAN SIKLUS KARBON GLOBAL - Mochamad Ramdhan Firdaus; Lady Ayu Sri Wijayanti (OSEANA, 2019)
PHYTOPLANKTON AND GLOBAL CARBON CYCLE. Scientists around the world believe that phytoplankton, although microscopic, have a large role in the global carbon cycle. Various research results show that the net primary productivity of all phytoplankton in the sea is almost as large as the net primary productivity of all plants on land. Phytoplankton through the process of photosynthesis absorbs 40-50 PgC / year from the atmosphere. Also, phytoplankton is known to be responsible for transporting carbon from the atmosphere to the seafloor through the carbon biological pump mechanism. Phytoplankton from the coccolithophores group is known to play a role in the sequestration of carbon on the seabed through the carbonate pump mechanism. The mechanism is capable of sequestering carbon for thousands of years on the seabed in the form of sedimentary rocks (limestone).